Las Revistas Académicas Electrónicas en Latinoamerica de Administración y Negocios (2013)
The beginnings of scientific journals were due to the need for communication between scientists, since the data on which they were based were libraries, laboratories and field work; it was necessary to go to the results that their colleagues had obtained, in this way the scientific journals emerge mainly as a means of disseminating information about the results of research carried out by scientists, since it was the way in which the scientific community managed to resort to these written sources, to rely on and rely on those experiences and thus be able to advance their research, taking into account that these publications should be of quality, peer reviewers appear, who in their main function should establish evaluation criteria. As a result of the above, the researchers began to have prestige according to the magazine where their articles were published.